Identification of the hub genes related to adipose tissue metabolism of bovine - Wang, Xiaohui; Wang, Jianfang; Raza, Sayed Haidar Abbas; Deng, Jiahan; Ma, Jing; Qu, Xiaopeng; Yu, Shengchen; Zhang, Dianqi; Alshammari, Ahmed Mohajja; Almohaimeed, Hailah M.; Zan, Linsen (Frontiers in Veterinary Science, 2022)
Due to the demand for high-quality animal protein, there has always been a lot of concern about how to produce more high-quality beef. Cattle with different energy or protein diet have obvious effects on the lipid metabolism of beef, and the adipose content of beef has a close connection with the taste and quality of beef. In this study, we performed weighted gene co-expression network analysis (WGCNA) with subcutaneous adipose genes from Norwegian red bulls fed different diets to identify hub genes regulating bovine lipid metabolism. Above all, the RNA sequencing data of subcutaneous adipose tissue of 12-month-old Norwegian red bull (n=48) with different energy or protein levels were selected from GEO database, and 7630 genes with the largest variation were selected for WGCNA analysis. A total of 21 gene co-expression modules were identified, and 15 gene modules were finally formed by combining similar modules. Then, three modules were selected as hub genes candidate modules according to the correlation between modules and phenotypes, and the genes in the modules were imported into online tools g:Profiler and KOBAS for GO and KEGG enrichment analysis. The interaction network between hub genes and their target genes was exported to Cytoscape to construct the gene interaction network. Finally, eight hub genes of lipid metabolism, TIA1, LOC516108, SNAPC4, CPSF2, ZNF574, CLASRP, MED15 and U2AF2, were identified in the three modules. The relative expression levels of hub genes in the heart, liver, spleen, lung, kidney, muscle and adipose tissue were also measured to verify the results. The correlation between the metabolism of subcutaneous adipose tissue and the intake of different energy and protein diets was analyzed. Furthermore, predicted the key genes of lipid metabolism in subcutaneous adipose tissue affected by intake of different energy diets to find the hub genes regulate lipid metabolism, which provide a theoretical basis for regulating beef quality.